Analisis Kelayakan Buku Bahasa Indonesia Kelas VI SD Berdasarkan Instrumen Standar BNSP - Tia Nur Kusuma Dwi Hastuti; Panca Dewi Purwati; Maitsaa Najwa Nadhifaa; Miftafus Zharimar; Achmad Ananda Wira Zalfitra; Roofid Nur Syauqi (Pusat riset dan Inovasi Nasional, 2025)
This research is motivated by the importance of evaluating Indonesian language textbooks in elementary schools to ensure they comply with the standards set by the National Education Standards Agency (BNSP).This research aims to describe the feasibility of the Indonesian Language textbook: Children Who Change the World for grade VI of elementary school based on the BNSP instrument, which includes aspects of content, language, presentation, and graphics. The approach used is descriptive qualitative with content analysis techniques on books published by the Book Center in 2022. The results of the study showed that the book obtained an average score of 80%, with the quality of content, language, and presentation being classified as good, although there were shortcomings in the cover and completeness of the book elements. This book is suitable for use with several improvements to increase its effectiveness as a teaching material.